2013
DOI: 10.1073/pnas.1218832110
|View full text |Cite
|
Sign up to set email alerts
|

Specific DNA recognition mediated by a type IV pilin

Abstract: Natural transformation is a dominant force in bacterial evolution by promoting horizontal gene transfer. This process may have devastating consequences, such as the spread of antibiotic resistance or the emergence of highly virulent clones. However, uptake and recombination of foreign DNA are most often deleterious to competent species. Therefore, model naturally transformable Gramnegative bacteria, including the human pathogen Neisseria meningitidis, have evolved means to preferentially take up homotypic DNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
174
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(190 citation statements)
references
References 37 publications
14
174
0
2
Order By: Relevance
“…We show that the force-dependent kinetics of DNA uptake are in remarkable agreement with a translocation ratchet model, whereby the periplasmic ComE protein acts as a chaperone that rectifies DNA diffusion through the outer membrane by reversible binding. strongly inhibited when comP is deleted (31,32). PilV has an antagonistic character, and its deletion increases the probability for DNA binding and uptake (33).…”
mentioning
confidence: 99%
“…We show that the force-dependent kinetics of DNA uptake are in remarkable agreement with a translocation ratchet model, whereby the periplasmic ComE protein acts as a chaperone that rectifies DNA diffusion through the outer membrane by reversible binding. strongly inhibited when comP is deleted (31,32). PilV has an antagonistic character, and its deletion increases the probability for DNA binding and uptake (33).…”
mentioning
confidence: 99%
“…Playing important roles in this process are the Type IV pilus (Tfp) and the DUS, a 10 nt sequence, 5¢-GCCGTCTGAA-3¢, that is highly enriched in neisserial genomes. Tfp-mediated DNA transformation involves, among other things, the binding of the DUS to Tfpassociated protein ComP, and PilT-driven retraction of the Tfp (Cehovin et al, 2013;Hamilton & Dillard, 2006;Wolfgang et al, 1998). Two DUS variants, distinguished by two bases immediately preceding the 10-mer, are abundant in neisserial genomes: 5¢-agGCCGTCTGAA-3¢ and 5¢-atGCCG TCTGAA-3¢.…”
Section: A Detailed Analysis Of Ap2031mentioning
confidence: 99%
“…Tfp consists of a fibre, composed mainly of pilin subunits, that extends from the cell into the extracellular milieu, and machinery for its assembly and many biological activities (Carbonnelle et al, 2006;Giltner et al, 2012). In addition to DNA tranformation (Cehovin et al, 2013;Wolfgang et al, 1998), Tfp plays important roles in other aspects of biology of the genus Neisseria, including bacterial attachment, motility, microcolony formation and signalling to the host cell (Eriksson et al, 2012;Helaine et al, 2005;Higashi et al, 2007;Howie et al, 2005;Kurre et al, 2012;Lee et al, 2005;Merz et al, 1996Merz et al, , 1999Merz et al, , 2000Nassif et al, 1994;Pujol et al, 1999;Winther-Larsen et al, 2001;Wolfgang et al, 1998). That AP2031 T /N.…”
Section: à5mentioning
confidence: 99%
“…The ComP protein in N. meningitidis has been identified as a likely DUS receptor with higher binding affinity for species-specific sequence than for nonspecific sequence (22). V. cholerae does not appear to restrict uptake to species-specific DNA, as Suckow et al have demonstrated the capacity of V. cholerae to take up DNA from other bacteria, such as Escherichia coli, into the periplasmic space between the IM and OM (23).…”
Section: The Competence Apparatusmentioning
confidence: 99%